A numerical and experimental study on motion responses of semi-submersible platforms subjected to short-crested waves - Kurian, V.J. (Krishtel eMaging Solutions Pvt. Ltd, 2015)
The effect of the short-crested waves on the motions of moored semi-submersible platform is demonstrated from the results of the model tests and has been compared with the theoretical calculations to validate the numerical simulations. The model tests were performed in the wave tank located in the Offshore Laboratory of UniversitiTeknologi PETRONAS. In the tests, the model was moored in the head sea with four linear springs fore and aft, and the motion responses subjected to multi-directional waves were measured. The responses in three degrees of freedom (DOF) (surge, heave and pitch) are presented. Two time domain numerical MATLAB codes incorporated with the long-crested wave and short-crested wave effect were developed. In the code, the mass, and stiffness matrices were calculated for each time step. The diffraction effect of long-crested and short-crested waveson circular cylinder was considered, and the equation of motion was solved by the Newmark Beta method. Responses in term of Response Amplitude Operator (RAO) are presented and compared. Good agreement between numerical and experimental results was achieved. The validated short-crested wave results were compared with the long-crested wave results. It was observed that the short-crested waves gave smaller responses in all DOF compared to the long-crested waves.